Application of Digital Platform Media Quizizz in Indonesian Language Subjects for Class VIII Students of SMP Muhammadiyah 01 Manado - Anggreyornai, Anggreyornai; Iroth, Santje; Luntungan, Grace (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study aims to explore the effectiveness of using the Quizizz digital platform in teaching procedural texts at SMP Muhammadiyah 01 Manado. With a qualitative approach, the research subjects consisted of Indonesian language teachers and grade VIII students. Data were collected through interviews, observations, documentation, questionnaires, and objective tests. The results showed that the use of Quizizz increased student participation and understanding of the material, with a success rate reaching 79%. Analysis of student scores showed an increase in accuracy in answering questions after using Quizizz, where most students scored above 80. However, some students still had difficulty with complex questions, indicating the need for additional explanations. This study confirms that the combination of technology use and direct guidance can significantly improve student understanding, as well as contribute to the development of innovative learning methods.